2023
DOI: 10.1021/acs.jafc.3c04154
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents, Bioactivities, and Pharmacological Mechanisms of Dendrobium officinale: A Review of the Past Decade

Ping Zhang,
Xingyu Zhang,
Xingyi Zhu
et al.

Abstract: Dendrobium officinale, a plant in the Orchidaceae family, has been used in traditional Chinese medicine for thousands of years. Sweet and slightly cold in nature, it can invigorate the stomach, promote fluid production, nourish Yin, and dissipate heat. Over the past decade, more than 60 compounds have been derived from D. officinale, including flavonoids, bibenzyl, and phenanthrene. Various studies have explored the underlying pharmacological mechanisms of these compounds, which have shown antitumor, hypoglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 123 publications
1
7
0
Order By: Relevance
“…Dendrobium nobile Lindl. has the anti-inflammatory, antibacterial and immunomodulatory effects in the field of modern medical research, suggesting that it could be considered as a therapeutic agent for UC [ 81 ]. Dendrobium officinale leaf phenolics could act in multiple ways to ameliorate DSS-induced colitis, mainly by decreasing the relative abundance of parasutterella_excrementihominis, ligilactobacillus_murinus, increasing the relative abundance of relative abundance of faecalibaculum_rodentium, and promoting the production of short-chain fatty acids; down-regulating the levels of TLR4, phosphorylated IKKα/β, and NF-κB p65, and inhibiting the expression of the TLR4/NF-κB inflammatory signalling pathway; and restoring zonula occludens 1, Occludin and Claudin-1 and other tight junction proteins expression to repair the intestinal barrier function; inhibiting the secretion of pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6 [ 82 ].…”
Section: Single Chinese Herbs For the Uc Treatmentmentioning
confidence: 99%
“…Dendrobium nobile Lindl. has the anti-inflammatory, antibacterial and immunomodulatory effects in the field of modern medical research, suggesting that it could be considered as a therapeutic agent for UC [ 81 ]. Dendrobium officinale leaf phenolics could act in multiple ways to ameliorate DSS-induced colitis, mainly by decreasing the relative abundance of parasutterella_excrementihominis, ligilactobacillus_murinus, increasing the relative abundance of relative abundance of faecalibaculum_rodentium, and promoting the production of short-chain fatty acids; down-regulating the levels of TLR4, phosphorylated IKKα/β, and NF-κB p65, and inhibiting the expression of the TLR4/NF-κB inflammatory signalling pathway; and restoring zonula occludens 1, Occludin and Claudin-1 and other tight junction proteins expression to repair the intestinal barrier function; inhibiting the secretion of pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6 [ 82 ].…”
Section: Single Chinese Herbs For the Uc Treatmentmentioning
confidence: 99%
“…Plant extracts are increasingly considered safer candidates for preventing glycation compared to synthetic compounds, as they have shown fewer adverse reactions in vivo and in vitro experiments. , Flavonoids, which are polyphenolic compounds highly abundant in plant extracts, exert satisfactory antiglycation activity . Flavonoid extracts from Chrysanthemum indicum, Teucrium polium, and Vaccinium vitisidaea were reported to inhibit the formation of products from different glycation stages, which may be related to their strong radical scavenging activity .…”
Section: Introductionmentioning
confidence: 99%
“…This plant has been used in traditional Chinese medicine for thousands of years used to protect the liver, treat cancer, gastritis, enhance immunity, stimulate digestion, reduce blood sugar and blood fat. 1,2 In Vietnam, D. officinale has been found in the mountains and forests of Vinh Phu, Quang Tri, Quang Nam, Da Nang, Gia Lai, Lam Dong provinces. The previous studies reported terpenoids, 3 bibenzyl derivatives, 1–7 polysaccharides, 8–15 are the main components of this plants.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In Vietnam, D. officinale has been found in the mountains and forests of Vinh Phu, Quang Tri, Quang Nam, Da Nang, Gia Lai, Lam Dong provinces. The previous studies reported terpenoids, 3 bibenzyl derivatives, 1–7 polysaccharides, 8–15 are the main components of this plants. Some of which exhibited antitumor, 7,14,15 anti-inflammatory activities 8–13 and alleviates type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%